Melatonin excretion in photoperiodic mammalian and bird species: chinchilla and Japanese quail - Dominchin, M. F.; Bianconi, S.; Ponzio, M. F.; Turina, A. V.; Labuckas, D.; Busso, J. M. (2024)
Fil: Dominchin, M. F. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina.